Case Report: Successful treatment of a case of Lynch syndrome with double primary ovarian and rectal cancer - Yu, Zhengliang; Yang, Gang; Yue, Jing; Liang, Haiyan; Yi, Man; Luo, Yong; Fu, Haixiao; Wang, Zhenran; Jian, Zhiyuan; Gao, Yi (Frontiers in Oncology, 2025)
BackgroundLynch syndrome (LS), previously known as hereditary nonpolyposis colorectal cancer (CRC), is an autosomal dominant disorder characterized by germline variants in the mismatch repair (MMR) gene (e.g., MLH1 and MSH2) with microsatellite instability (MSI), which leads to the development of CRC in 80% of cases with LS. Proximal colon is always involved in LS. LS is accompanied by an increased risk of developing glioblastoma, gastric cancer, and colorectal, endometrial, urothelial (ureteral and bladder), small intestinal, ovarian, biliary tract, and skin tumors (keratoacanthomas and sebaceous adenomas). The U.S. Food and Drug Administration has approved the use of pembrolizumab in the treatment of solid tumors with MMR defects or high MSI. Studies have shown that CRCs with MMR pathway loss-of-function variants respond favorably to PD-1 blockade immunotherapy.Case presentationIn this study, we report a case of LS in a 39-year-old female patient with concurrent ovarian and rectal adenocarcinoma. She showed high MSI, “pathogenic” germline variants in the MSH2 gene, and high tumor mutation burden. As a treatment modality, we chose a combination of immune checkpoint inhibitors, chemotherapy, and surgery and achieved a clinical complete response.ConclusionThis report is aimed at providing a reference for the diagnosis and treatment of tumors related to lynch syndrome, highlighting the diagnostic process of LS, and reporting treatment strategy of tumors related to lynch syndrome with the combination of immune checkpoint inhibitors, chemotherapy, and surgery.